Efficacy of zenocutuzumab in NRG1 fusion-positive cancer - Schram, Alison; Goto, Koichi; Kim, Dong-Wan; Macarulla, Teresa; Hollebecque, Antoine; O’Reilly, Eileen M.; Ou, Sai-Hong Ignatius; Rodon, Jordi; Rha, Sun Young; Nishino, Kazumi; Duruisseaux, Michaël; Park, Joon Oh; et al. (The New England journal of medicine, 2025)
A basket study evaluated the efficacy of zenocutuzumab, a bispecific antibody against HER2 and HER3, in patients with solid tumors harboring NRG1 fusions. Among 158 patients, 30% had a response (including 42% with pancreatic cancer).
Gesehen am 09.12.2025